Bakery properties of composite mixtures of wheat and spelt flour - N. S. Sanzharovskaya; N. V. Sokol; O. P. Khrapko; K. S. Mamedov; N. N. Romanova (Новые технологии, 2018)
Baking properties of the composite mixtures of flour (wheatand spelt) have been assessed. It ‘s shown that the introduction of spelt flour into the mixture leads to an increase in the activity of amylolytic enzymes. A decrease in the mass fraction of raw gluten in all samples of dough with the introduction of selt flour is observed. According to the results of experimental studies, the introduction of spelt flour in the amount of 40% will ensure the functional properties of finished products.